The Resistance Comparison Method Using Integral Controller for Photovoltaic Emulator - Razman Ayop; Chee Wei Tan; Cheng Siong Lim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
A Photovoltaic (PV) emulator is a device that produces a similar output as the PV module and it is useful for testing the PV generation system. This paper present a new and simple control strategy for the PV emulator using the combination of the Resistance Comparison Method with the Integral Controller. The closed-loop buck converter system with the current-mode controlled and the single diode model are used for the PV emulator. The results obtained from the proposed PV emulator are compared with the conventional PV emulator using the Direct Referencing Method as the control strategy. The proposed PV emulator produces a more accurate output, 74 % faster transient response, and a lower output voltage ripple compared to the conventional PV emulator.